Economic Analysis of the Eucalyptus Sector on Strengthening the Financial Stability of Eucalyptus Farmers in Burundi - Niyintunze, Simeon; Manirakiza, Diomede; Maniriho, Aristide; Karangwa, Antoine; Niyuhire, Marie Chantal (European Scientific Journal, ESJ, 2026)
This study aims to analyze the influence of the eucalyptus sector on strengthening the financial stability and economic resilience of rural households in Burundi, by assessing its capacity to function as a true "green bank" to finance productive investments. To this end, the methodology relies on a two-stage stratified comparative and probabilistic approach between two provinces with marked agro-ecological and socio-economic contrasts: the peri-urban area of Bujumbura and the highland regions of Burunga. Using the KoboCollect tool, direct surveys were conducted with a statistically robust sample of 190 farming households distributed across 4 communes and 9 hills. The data collected were then integrated into an econometric model of the determinants of global income using the ordinary least squares (OLS) method, analyzing the impact of 13 distinct sources of income and validated by rigorous tests of multicollinearity (VIF) and heteroscedasticity. The research results reveal a major economic dependence of farmers on this resource, evidenced by a near-perfect correlation of 98% between income from eucalyptus and overall household income. The econometric analysis specifies that a 1% increase in income from eucalyptus leaves leads to a 1.03% increase in total income, while a 1% increase in timber income results in a rise of nearly 1.00%. These financial gains allow families to make significant structural investments to sustainably improve their living conditions. In fact, households prioritize housing (23%), resulting in the modernization of dwellings and the complete disappearance of traditional huts, and access to healthcare (22%). The remaining earnings actively support human capital and family wealth through the financing of education (17%), food security (18%), the purchase of land plots (12.6%) and the development of livestock farming, particularly cattle farming at a rate of 54%.